Non-contrast computed tomography of type A acute aortic dissection in patients with out-of-hospital cardiopulmonary arrest: a case series. Issue 4 (6th December 2019) - Takeuchi, Shinsuke; Yamaguchi, Yoshihiro; Yoshino, Hideaki
Abstract: Background: The prognosis of patients admitted for acute aortic dissection (AAD) has remarkably improved. However, we must also consider out-of-hospital cardiopulmonary arrest (OHCPA) patients while assessing the prognosis. In recent years, autopsy imaging has become more common as an alternative to conventional autopsy. Therefore, we reviewed our OHCPA patients with type A AAD using acute phase non-contrast computed tomography (CT). Case summary: Here, we report a case series of three patients who developed OHCPA and were diagnosed with type A AAD using non-contrast CT. Although the direct causes of death varied in each case, we could easily determine the direct causes of death from clinical course of the condition and from non-contrast CT. Discussion: Although non-contrast CT does not completely replace autopsy, if its convenience and non-invasiveness make it possible for more patients to undergo the procedure, the real prognosis (including morbidity and mortality) may be better understood. Therefore, we considered it significant to use non-contrast CT for investigating the cause of sudden death.